How uro-oncology has been affected by COVID-19 emergency? Data from Piedmont/Valle d'Aosta Oncological Network, Italy. Issue 1 (February 2021) - Oderda, Marco; Calleris, Giorgio; Falcone, Marco; Fasolis, Giuseppe; Muto, Giovanni; Oderda, Gianluca; Porpiglia, Francesco; Volpe, Alessandro; Bertetto, Oscar; Gontero, Paolo
Introduction: Coronavirus disease 2019 (COVID-19) pandemic has dramatically hit all Europe and Northern Italy in particular. The reallocation of medical resources has caused a sharp reduction in the activity of many medical disciplines, including urology. The restricted availability of resources is expected to cause a delay in the treatment of urological cancers and to negatively influence the clinical history of many cancer patients. In this study, we describe COVID-19 impact on uro-oncological management in Piedmont/Valle d'Aosta, estimating its future impact. Methods: We performed an online survey in 12 urological centers, belonging to the Oncological Network of Piedmont/Valle d'Aosta, to estimate the impact of COVID-19 emergency on their practice. On this basis, we then estimated the medical working capacity needed to absorb all postponed uro-oncological procedures. Results: Most centers (77%) declared to be "much"/"very much" affected by COVID-19 emergency. If uro-oncological consultations for newly diagnosed cancers were often maintained, follow-up consultations were more than halved or even suspended in around two out of three centers. In-office and day-hospital procedures were generally only mildly reduced, whereas major uro-oncological procedures were more than halved or even suspended in 60% of centers. To clear waiting list backlog, the urological working capacity should dramatically increase in the next months; delays greater than 1 month are expected for more than 50% of uro-oncological procedures. Conclusions: COVID-19 emergency has dramatically slowed down uro-oncological activity in Piedmont and Valle d'Aosta. Ideally, uro-oncological patients should be referred to COVID-19-free tertiary urological centers to ensure a timely management.